Long-Term Consequences: Deep Time in Barry Lopez’s “The Stone Horse” - Norma Tilden (Transatlantica)
As a literary artifact of deep time, Barry Lopez’s essay “The Stone Horse” anticipates the building of the Clock of the Long Now, a project of the Long Now Foundation designed to foster long-term thinking and ecological stewardship. Lopez’s essay describes the writer’s encounter with an earthwork fashioned by Quechan artists perhaps four centuries ago in a California desert. The image is not carved into the hard desert pavement, but constructed from a process of re-arranging small stones and scraping dirt away. Lopez portrays the horse as subtractive art, coaxed out of the land by precise, sustained attention to particularities of natural contour and set in motion by the light of the sun moving across the desert floor. As an earthwork, the stone horse provides a material analogy to Lopez’s essay, a narrative confirmation of the non-reducible materiality of a physical site as it has existed through time. Lopez presents the desert as an archive, a lithic scripture reaching far below the stratum of Western man, which he reads as a transient history of comings and goings, as well as dizzying shifts in sovereignty set against the enduring presence of the horse.